Reengineering the Organisation Design of Wine Businesses - Afxentiou, Georgios; Melanthiou, Yioula (My University, 2022)
Organisational design is an established literature stream within organisation studies (Turner, R., & Miterev, M., The Organizational Design of the Project-Based Organization. Journal of Project Management, 50(4), 487–498. https://doi.org/10.1177/8756972819859746, 2019; Van de Ven et al., Perspectives on Innovation Processes. The Academy of Management Annals, 7(1). https://doi.org/10.1080/19416520.2013.791066, 2013) that addresses the antecedents, interactions and consequences of various facets of an organisation. The globalisation of wine businesses depends amongst others on internal factors such as abilities, attitudes, perception and culture of management and characteristics of a firm: organisation, resources and capabilities (Kesler et al., 2016). Wine businesses face crises and obstacles in penetrating the global market with evidence of limited export revenues. This study aimed to identify the factors influencing the formulation of a successful export strategy by wine businesses. A qualitative method was integrated with a secondary analysis of European and national statistical reports, surveys, articles and papers.